Бирюзовая маска: [роман] / Филлис Уитни - Уитни Филлис (Библиотека любовного романа, 1993)
Экземпляры: Аб (20090514) / Инвентарный номер: 94601 / Цена: 35.00 / Авт.знак: У 39 / ГРНТИ: 17.82 / ББК: 84(7Сое)